ANALISA DAMPAK SEBELUM DAN SESUDAH SPIN-OFF PADA PROFITABILITAS: STUDI KASUS PADA UNIT USAHA SYARIAH DI INDONESIA - Dety Nurfadilah; Sudarmawan Samidi (Jurnal Ekonomi dan Industri, 2019)
The purpose of this study is to analyze the impact before and after the spin-off of the Sharia Business Unit into a Sharia Commercial Bank on profitability. The data used in this study are ROA, ROE, and EPS which are divided into two periods, namely before the spin-off (2003-2009) and after the spin-off (2011-2017). Paired sample t-test and descriptive analysis of profitability performance are used to analyze data. The results of the study stated that there was a significant difference in ROE before and after the spin-off. However, there were no significant differences in ROA and EPS in the same two periods.